Use of Fermented Japanese Papaya (Cindoscolus Aconitifolius) Leaf Flour as an Alternative Feed to Increase the Production and Quality of Tilapia (Oreochromis Niloticus) - Rejeki, I Gusti Ayu Dewi Seri; Arya, I Wayan; Suryani, Sang Ayu Made Putri (PT FORMOSA CENDEKIA GLOBAL, 2024)
Tilapia (Oreochromis niloticus) is a type of aquaculture commodity that has high economic value as a freshwater consumption fish in the world. Efforts to increase the quantity and quality of commercial feed have an impact on the operational costs of intensive fish farming, namely more than (60-70%) of the total production costs. One effort to overcome dependence on imported feed raw materials is the use of local raw materials. The local raw materials used must have high nutritional value, be non-toxic, relatively cheap, very abundant and not compete with human needs, including Japanese papaya leaves. The use of Japanese papaya leaf flour as a source of carbohydrates and protein in fish feed cannot be done optimally because it contains high levels of fiber and tannin which can bind the minerals needed by fish.